LITERACY IN THE MIDST OF THE PANDEMIC: HOW ARE STUDENTS' LITERACY SKILLS? - Arif Widodo; Umar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
During the pandemic, learning at elementary schools encountered numerous obstacles, particularly in the area of literacy. One key indicator of basic literacy skills is reading fluency and comprehension. This study aimed to determine the profile of students’ basic literacy skills during the pandemic. The research was conducted at one of the public elementary schools in Kabupaten Lombok Tengah using a survey design with a test instrument. The subjects were 110 students selected through a saturated sampling technique. Data were analyzed using descriptive statistics. The results showed that 7% of students were at the beginner level, 10% were at the letter level, 11% were at the word level, 12% were at the paragraph level, and 12% were at story one level, while 48% of students reached the story level. Most students were not fluent in reading and were unable to understand the reading content. Students who were fluent and capable of understanding the text were less than half of the total population, amounting to only 48 out of 110 students. These findings indicate a decline in basic literacy skills among students during the pandemic learning period.